1999
DOI: 10.1016/s0022-5347(05)68270-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With Finasteride Daily Does Not Affect Spermatogenesis or Semen Production in Young Men

Abstract: Treatment with 1 mg. finasteride daily for 48 weeks did not affect spermatogenesis or semen production in young men. The effects of 1 mg. finasteride daily on prostate volume and serum PSA in young men without benign prostatic hyperplasia were small and reversible on discontinuation of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Variable findings for the effects of finasteride on human male fertility have also been reported. One study randomized 181 men to take finasteride 1 mg/day or placebo for 1 year . Seventy‐nine of the 181 participants had semen analyzed, which showed no significant differences on sperm concentration, morphology, and motility, between the experimental and control groups .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable findings for the effects of finasteride on human male fertility have also been reported. One study randomized 181 men to take finasteride 1 mg/day or placebo for 1 year . Seventy‐nine of the 181 participants had semen analyzed, which showed no significant differences on sperm concentration, morphology, and motility, between the experimental and control groups .…”
Section: Resultsmentioning
confidence: 99%
“…One study randomized 181 men to take finasteride 1 mg/day or placebo for 1 year . Seventy‐nine of the 181 participants had semen analyzed, which showed no significant differences on sperm concentration, morphology, and motility, between the experimental and control groups . In contrast, a report of two infertile males with severe oligospermia or azoospermia demonstrated that 6 months after finasteride was discontinued, sperm concentration significantly improved .…”
Section: Resultsmentioning
confidence: 99%
“…However, in a randomized double‐blind, placebo‐controlled study on young men, semen samples were analysed in 40 men, who received 1 mg finasteride (5 α ‐reductase type 2 inhibitor) daily for 48 weeks, whereas 39 men received placebo. No effect of the compound on semen volume, sperm concentration, total sperm count, sperm motility or serum levels of FSH, LH and testosterone was found (Overstreet et al. , 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions. Subjects treated with finasteride 1 mg/day may occasionally have adverse reactions, such as libido or ejaculated semen reduction, erection problems (8,11–16). It is possible to have multiple side effects simultaneously.…”
mentioning
confidence: 99%